Thermoelectric device and preparation method and application thereof
Thermoelectric devices were fabricated by combining electrospinning and spraying to construct a continuous three-dimensional conductive network. This solved the problem of interface delamination of existing flexible thermoelectric materials under complex deformation, achieving high conductivity and mechanical durability, and making them suitable for temperature and strain sensing in wearable devices.
Patent Information
- Application Number
- CN202511110131.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-11-14
AI Technical Summary
Existing flexible thermoelectric materials have poor uniformity of conductive network, low carrier mobility, and are prone to interface delamination under complex deformation, making it difficult to meet the long-term stable application requirements of wearable devices in complex human movement scenarios.
Thermoelectric devices are fabricated using a combination of electrospinning and spraying. A continuous three-dimensional conductive network is constructed by alternately stacking fiber membranes and conductive layers. The pores of the fiber membrane are filled by an impregnation process, resulting in good mechanical strength and conductivity.
The fabricated thermoelectric device has high electrical conductivity, Seebeck coefficient and power factor, good mechanical durability and flexibility, can operate stably in complex human motion scenarios, realize temperature and strain sensing, and is suitable for wearable devices.
Smart Images

Figure CN120957588A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermoelectric device fabrication, specifically relating to a thermoelectric device, its fabrication method, and its application. Background Technology
[0002] With the rapid development of the Internet of Things, artificial intelligence, and mobile healthcare technologies, flexible wearable devices are gradually evolving from single-function sensors to self-powered, multi-functional integrated systems. Currently, wearable devices generally rely on rigid electronic components and external power supplies, resulting in insufficient mechanical flexibility, limited wearing comfort, and weak battery life, making it difficult to meet the needs of long-term stable monitoring in complex human movement scenarios.
[0003] Thermoelectric materials have attracted much attention because they can directly utilize the temperature gradient between the human body and the environment to generate electricity continuously. Flexible thermoelectric materials can solve the above-mentioned technical problems.
[0004] In existing technologies, the development of flexible thermoelectric materials mainly focuses on organic / inorganic composite systems. For example, active components such as carbon nanotubes and conductive polymers are combined with an elastomer matrix to achieve both thermoelectric performance and mechanical flexibility. However, most existing flexible thermoelectric materials are prepared by spraying or impregnating active components onto an elastic matrix. The resulting thermoelectric materials have poor uniformity of the conductive network and low carrier mobility. Furthermore, when the elastic matrix has a multilayer structure, there is a risk of interfacial delamination under complex deformation, which seriously limits the reliability of practical applications. Summary of the Invention
[0005] The purpose of this invention is to provide a thermoelectric device, its preparation method, and its application, in order to solve the aforementioned technical problems.
[0006] To achieve the above objectives, the present invention provides a method for fabricating a thermoelectric device, comprising: providing an electrospinning solution and a conductive liquid; the electrospinning solution comprising thermoplastic polyurethane; the conductive liquid comprising multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate; electrospinning the electrospinning solution to obtain a fiber membrane; spraying the conductive liquid onto the surface of the fiber membrane and drying to form a conductive layer; repeating the steps of electrospinning, spraying, and drying to obtain a primary fiber membrane-conductive filler composite; the primary fiber membrane-conductive filler composite comprising alternating layers of the fiber membrane and the conductive layer; immersing the primary fiber membrane-conductive filler composite in the conductive liquid, removing it, washing it, and drying it to obtain a fiber membrane-conductive filler composite; cutting the fiber membrane-conductive filler composite into multiple sub-devices with a predetermined shape, and connecting the multiple sub-devices through a conductor.
[0007] Optionally, the mass percentage of thermoplastic polyurethane in the electrospinning solution is 23wt% to 27wt%; and / or, the solid content of the conductive liquid is 3mg / ml to 5mg / ml.
[0008] Optionally, the electrospinning solution is formed by dissolving thermoplastic polyurethane particles in an organic solvent; the organic solvent includes N,N-dimethylformamide and tetrahydrofuran, and the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 1:(0.8-1.2); or, the organic solvent includes N,N-dimethylformamide and acetone, and the volume ratio of N,N-dimethylformamide to acetone is 1:(0.8-1.2); or, the organic solvent includes dimethylacetamide and tetrahydrofuran, and the volume ratio of dimethylacetamide to tetrahydrofuran is 1:
[0009] (0.8~1.2).
[0010] Optionally, the conductive liquid is formed by ultrasonically dispersing multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in deionized water; the mass ratio of multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid is greater than 0 and less than 10.
[0011] Optionally, the mass ratio of multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid is one of 1:4, 1:1, or 4:1.
[0012] Optionally, the voltage during electrospinning is 12kV to 15kV, the distance between the electrospinning nozzle and the collector for fiber deposition is 15cm to 20cm, the flow rate of the electrospinning solution is 1.5ml / h to 2.5ml / h, the thickness of the fiber membrane is 25μm to 100μm, and / or the number of repetitions of the electrospinning, spraying, and drying steps is less than or equal to 7.
[0013] Optionally, when the conductive liquid is sprayed onto the surface of the fiber membrane, the amount of conductive liquid sprayed is 3ml to 8ml, and the coverage of the conductive liquid on the surface of the fiber membrane is greater than or equal to 95%.
[0014] Optionally, the primary fiber membrane-conductive filler composite is immersed in the conductive liquid for 30 min to 60 min.
[0015] To achieve the above objectives, the present invention also provides a thermoelectric device, which is fabricated using the method described in any of the preceding claims; the thermoelectric device has an electrical conductivity greater than or equal to 80 S·m. -1 The Seebeck coefficient is 20 μV·K. -1 ~25μV·K -1The power factor is 30 nW·m -1 ·K -2 ~70 nW·m -1 ·K -2 Tensile strength greater than or equal to 20 MPa, and elongation at break greater than 200%.
[0016] To achieve the above objectives, the present invention also provides an application of the thermoelectric device as described above.
[0017] Compared with the prior art, the thermoelectric device and its preparation method and application of the present invention have the following advantages: The aforementioned preparation method of the thermoelectric device includes: providing an electrospinning solution and a conductive liquid; the electrospinning solution includes thermoplastic polyurethane; the conductive liquid includes multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate; electrospinning the electrospinning solution to obtain a fiber membrane; spraying the conductive liquid onto the surface of the fiber membrane and drying to form a conductive layer; repeating the steps of electrospinning, spraying, and drying to obtain a primary fiber membrane-conductive filler composite, the primary fiber membrane-conductive filler composite including multiple fiber membranes and multiple conductive layers stacked alternately; immersing the primary fiber membrane-conductive filler composite in the conductive liquid, removing it, washing it, and drying it to obtain a fiber membrane-conductive filler polymer; cutting the fiber membrane-conductive filler composite into multiple sub-devices with a predetermined shape, and connecting the multiple sub-devices through a conductor; the thermoelectric device prepared by this preparation method has a conductivity greater than or equal to 80 S·m. -1 The Seebeck coefficient is 20 μV·K. -1 ~25μV·K⁻¹, power factor of 30nW·m -1 ·K -2 ~70 nW·m -1 ·K -2 With a tensile strength greater than or equal to 20MPa and an elongation at break greater than 200%, it possesses mechanical durability and flexibility suitable for wearable devices and adaptable to long-term deformation and stable operation under complex human movement scenarios. It can also achieve temperature sensing and strain sensing, meeting the application needs of multiple scenarios such as medical health and motion analysis. Attached Figure Description
[0018] The accompanying drawings are provided to better understand the invention and are not intended to unduly limit the scope of the invention.
[0019] Figure 1 This is a flowchart of a method for preparing a thermoelectric device according to an embodiment of the present invention.
[0020] Figure 2 This is a schematic diagram of the structure of the primary fiber membrane-conductive filler composite prepared according to the method for preparing thermoelectric devices provided in an embodiment of the present invention.
[0021] Figure 3 This is a scanning electron microscope image of the fiber membrane prepared in the method for preparing thermoelectric devices according to the first embodiment of the present invention.
[0022] Figure 4 This is a scanning electron microscope image of the fiber membrane-conductive filler composite prepared in the method for preparing thermoelectric devices according to the first embodiment of the present invention.
[0023] Figure 5 This is a comparison chart of the conductivity and Seebeck coefficient of the thermoelectric devices prepared according to the preparation methods of the first to third embodiments, the first comparative example and the second comparative example of the present invention.
[0024] Figure 6 This is the open-circuit voltage output curve of the thermoelectric device prepared according to the method of preparing thermoelectric device provided in the first embodiment of the present invention under different temperature difference conditions.
[0025] Figure 7 This is a stress-strain curve diagram of the thermoelectric device prepared according to the preparation method of the thermoelectric device provided in the first to third embodiments of the present invention.
[0026] Figure 8 This is a schematic diagram showing the voltage response changes of a finger bent at 45° and 90° under a temperature gradient of 10K, based on the thermoelectric device prepared by the method provided in the first embodiment of the present invention.
[0027] Figure 9 This is a scanning electron microscope image of the fiber membrane-conductive filler composite prepared in the method for preparing thermoelectric devices according to the first comparative example of the present invention.
[0028] Figure 10 This is a scanning electron microscope image of the fiber membrane-conductive filler composite prepared in the method for preparing thermoelectric devices according to the second comparative example of the present invention.
[0029] Figure reference numerals: 10 - fiber membrane, 20 - conductive layer. Detailed Implementation
[0030] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in this embodiment are only schematic representations of the basic concept of the present invention. Therefore, the drawings only show components related to the present invention and are not drawn according to the actual number, shape, and size of components in the actual implementation. In the actual implementation, the type, quantity, and proportion of each component can be arbitrarily changed, and the component layout may also be more complex.
[0031] Furthermore, while each embodiment described below possesses one or more technical features, this does not imply that users of the present invention must simultaneously implement all technical features in any embodiment, or can only separately implement some or all technical features in different embodiments. In other words, provided it is feasible, those skilled in the art can, based on the disclosure of the present invention and depending on design specifications or implementation requirements, selectively implement some or all technical features in any embodiment, or selectively implement a combination of some or all technical features in multiple embodiments, thereby increasing the flexibility in implementing the present invention.
[0032] As used herein, the singular forms “a,” “an,” and “the” include plural objects, and the plural form “a plurality” includes two or more objects, unless otherwise expressly indicated. As used herein, the term “or” is generally used to include the meaning of “and / or,” unless otherwise expressly indicated, and the terms “install,” “connect,” and “link” should be interpreted broadly, for example, as a fixed connection, a detachable connection, or an integral connection. Connections can be mechanical or electrical. Connections can be direct or indirect through an intermediate medium, and can represent internal communication between two elements or an interaction between two elements. Those skilled in the art will understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0033] As described in the background art, the thermoelectric materials prepared by loading active components onto an elastic substrate through spraying or impregnation in the prior art have poor performance. The applicant of this application conducted in-depth research and found that when loading active components onto an elastic substrate by spraying, the active components only remain on the surface of the elastic substrate and cannot penetrate the internal pores, resulting in insufficient lateral conductivity of the prepared flexible thermoelectric material. When loading active components onto a multilayered elastic substrate by impregnation, the active components can fill the internal pores of the elastic substrate, achieving intralayer conductivity in each layer, but continuous interlayer channels cannot be constructed between the layers. This leads to problems such as interface peeling and reduced longitudinal carrier mobility under complex deformation.
[0034] In view of this, embodiments of the present invention provide a method for fabricating a thermoelectric device, which aims to solve the above problems through a synergistic process of spraying and impregnation.
[0035] To make the objectives, advantages, and features of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. It should be noted that the drawings are all in a very simplified form and use non-precise proportions, and are only used to facilitate and clearly illustrate the objectives of the embodiments of the present invention. The same or similar reference numerals in the drawings represent the same or similar parts.
[0036] Figure 1 A flowchart illustrating the fabrication method of the thermoelectric device provided in an embodiment of the present invention is shown. Figure 1 As shown, the preparation method includes the following steps S1 to S5.
[0037] Step S1 includes providing an electrospinning solution and a conductive solution.
[0038] Step S2 includes electrospinning the electrospinning solution to obtain a fiber membrane 10 (e.g., ...). Figure 2 (As shown).
[0039] Step S3 includes spraying the conductive liquid onto the surface of the fiber membrane and drying it to form a conductive layer 20 (e.g., ...). Figure 2 (As shown).
[0040] Repeat steps S2 and S3 to obtain a primary fiber membrane-conductive filler composite.
[0041] Step S4 includes immersing the primary fiber membrane-conductive filler composite in the conductive liquid, removing it, washing it, and drying it to obtain the fiber membrane-conductive filler composite.
[0042] Step S5 includes cutting the fiber membrane-conductive filler composite into multiple sub-devices with a preset shape, and connecting the multiple sub-devices with a conductor.
[0043] The electrospinning solution comprises thermoplastic polyurethane (TPU). The conductive liquid comprises multi-walled carbon nanotubes (MWCMT) and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PETDOT:PSS).
[0044] The structure of the primary fiber membrane-conductive filler composite is as follows: Figure 2 As shown, it includes a plurality of alternately stacked fiber membranes 10 and a plurality of conductive layers 20.
[0045] In the above preparation method, by repeatedly performing step S2, the substrate of the electrothermal device (i.e., the fiber membrane-conductive filler composite) comprises multiple layers of the fiber membrane 10, thus possessing good mechanical strength. By spraying conductive liquid onto the surface of each fiber membrane 10 to form the conductive layer 20, a longitudinal conductive pathway between layers is constructed, which is beneficial for improving the longitudinal mobility of charge carriers. The conductive liquid is impregnated to fill the pores within the layers of the fiber membrane 10, and after curing, a conductive filler is formed, achieving lateral conductivity within the layers and establishing lateral conductive pathways within the layers. Therefore, the conductive filler within the pores of the fiber membrane 10 and the interlayer conductive layers 20 together establish a continuous three-dimensional conductive network, reducing the interfacial resistance between adjacent fiber membrane layers 10, thereby reducing the risk of deformation and peeling between adjacent fiber membrane layers 10. Therefore, the thermoelectric device prepared by the above method exhibits good flexibility and possesses both temperature and strain response capabilities. This enables the thermoelectric device to be applied to smart wearable devices and adapt to long-term deformation and stable operation under complex human movement scenarios. Furthermore, it can achieve temperature and strain sensing, meeting the needs of multiple scenarios such as medical health and motion analysis. In practice, the thermoelectric device prepared by the method of this embodiment has a tensile strength greater than or equal to 20 MPa, an elongation at break greater than 200%, preferably greater than or equal to 250%, and a Seebeck coefficient of 20 μV·K. -1 ~25μV·K -1 Electrical conductivity greater than or equal to 80 S·m -1 The power factor is 30 nW·m -1 ·K -2 ~70 nW·m -1 ·K -2 Here, the power factor is calculated based on formula (1), which is: PF = S 2 ·σ, where PF represents the power factor, S represents the Seebeck coefficient, and σ represents the conductivity.
[0046] Here, "longitudinal" refers to the arrangement direction of each layer of the fiber membrane 10, and "transverse" is perpendicular to the longitudinal direction. The conductive filler includes multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid.
[0047] In step S1, the electrospinning solution is formed by dissolving thermoplastic polyurethane particles in an organic solvent, and its concentration (mass percentage) is 23wt% to 27wt%.
[0048] The organic solvent comprises at least two components. In some embodiments, the organic solvent comprises N,N-dimethylformamide and tetrahydrofuran, wherein the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 1:(0.8–1.2). In other embodiments, the organic solvent comprises N,N-dimethylformamide and acetone, wherein the volume ratio of N,N-dimethylformamide to acetone is 1:(0.8–1.2). In still other embodiments, the organic solvent comprises dimethylacetamide and tetrahydrofuran, wherein the volume ratio of dimethylacetamide to tetrahydrofuran is 1:(0.8–1.2).
[0049] The process for preparing the electrospinning solution is as follows: thermoplastic polyurethane particles are placed in the organic solvent and magnetically stirred at approximately 60°C for about 6 hours to ensure complete dissolution of the thermoplastic polyurethane particles. Subsequently, the solution is allowed to stand for approximately 30 minutes to remove air bubbles.
[0050] In step S1, the conductive liquid is formed by mixing multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in deionized water and then ultrasonically dispersing them. The specific preparation process can be as follows: first, a predetermined amount of multi-walled carbon nanotube aqueous dispersion and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate aqueous dispersion are mixed; then, deionized water is added according to the actual situation to make the solid content in the mixture 3 mg / ml to 5 mg / ml; then, the mixture is ultrasonically dispersed using an ultrasonic cell disruptor; finally, it is allowed to stand to eliminate the concentration gradient caused by local thermal effects. During the dispersion process, the ultrasonic cell disruptor has a power of 400W and a frequency of 40kHz. Through ultrasonic dispersion, the sulfonic acid groups in poly(3,4-ethylenedioxythiophene):polystyrene sulfonate can bind to the surface of multi-walled carbon nanotubes through π-π conjugation, effectively inhibiting nanotube aggregation and simultaneously improving carrier mobility.
[0051] The mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid should be appropriate to optimize carrier mobility through π-π conjugation. In practice, the mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate can be greater than 0 and less than 10, for example, any one of 1:4, 1:1, or 4:1, or other ratios are also possible. Such a mass ratio can improve the conductivity of the prepared thermoelectric device by more than 30% compared to the prior art.
[0052] It is easy to understand that each execution of step S2 forms one layer of the fiber membrane 10. In practice, the number of times step S2 is executed, n, is less than or equal to 7, so that the number of fiber membrane 10 layers in the prepared thermoelectric device is no more than 7. The reason for this is that if the number of fiber membrane 10 layers is too large, the conductivity of the thermoelectric device will decrease, thus affecting its performance.
[0053] The thickness of each fiber membrane 10 is 25 μm to 100 μm. The thickness of the fiber membrane 10 is controlled by the parameters of electrospinning. Specifically, each time step S2 is performed, the voltage during electrospinning is 12 kV to 15 kV, the distance between the electrospinning nozzle and the collector for fiber deposition is 15 cm to 20 cm, the flow rate of the electrospinning solution is 1.5 ml / h to 2.5 ml / h, and the electrospinning time is 0.5 h to 1.5 h.
[0054] Step S3 is performed once after each execution of step S2, and the number of times step S3 is performed is equal to the number of times step S2 is performed. Each time step S3 is performed, the amount of conductive liquid sprayed is 3ml to 8ml, and the coverage of the conductive liquid on the surface of the fiber membrane is greater than or equal to 95%. In actual operation, an air spraying device is used to spray the conductive liquid onto the fiber membrane 10. The air pressure of the air spraying device is 0.2MPa to 0.4MPa, the inner diameter of the nozzle is 0.3mm to 0.8mm, and the spraying distance is 10cm to 20cm.
[0055] In step S3, the conductive liquid sprayed on the fiber membrane 10 can be dried in any suitable manner, such as by using a hot air drying oven at a temperature of 45°C to 60°C for a duration of 15 min to 30 min.
[0056] In step S4, the primary fiber membrane-conductive filler composite is immersed in the conductive liquid for 30 min to 60 min, so that the conductive liquid can fully penetrate into the pores of the fiber membrane 10 under capillary action, and together with the conductive layer 20 formed by spraying, form a continuous three-dimensional conductive network.
[0057] In step S4, the impregnated primary fiber membrane-conductive filler composite is cleaned with deionized water to remove loose conductive filler that is not bonded to the fiber membrane 10. The cleaning process can be completed when the pH of the deionized water used to rinse the impregnated primary fiber membrane-conductive filler composite is 6-7 at room temperature.
[0058] In step S4, the primary fiber membrane-conductive filler composite that has undergone impregnation and cleaning can be dried using any suitable method, such as a vacuum drying oven at a temperature of 40°C to 50°C for 60 to 90 minutes. Drying in a vacuum environment facilitates the rapid evaporation of the organic solvent in the conductive liquid.
[0059] In step S5, the preset shape can be any suitable shape such as rectangle, wave, or ellipse; this embodiment of the invention does not limit this. The specific steps for connecting multiple sub-devices via a conductor are as follows: multiple sub-devices are connected using electrodes, and then silver paste is coated onto the connection area between the electrodes and the sub-devices. The electrodes are, for example, copper foil electrodes. The purpose of coating with silver paste is to reduce the contact resistance between the electrodes and the sub-devices.
[0060] In some embodiments, it is preferable that after step S5, the multiple connected sub-devices and electrodes are encapsulated within a polymer film. The polymer film possesses good flexibility and sealing properties; optional polymer films include, for example, polyimide films with a thickness of 45 μm to 55 μm or other films with similar properties. The purpose of encapsulation is twofold: firstly, to protect the sub-devices and electrodes to ensure the mechanical stability of the thermoelectric device; and secondly, to prevent the conductive filler on the sub-devices from detaching and causing environmental pollution.
[0061] A second objective of this invention is to provide a thermoelectric device, which is prepared by the aforementioned method for preparing thermoelectric devices.
[0062] A third objective of this invention is to provide an application of the thermoelectric device as described above, specifically its application in the field of sensors. This sensor can be a temperature sensor, which can be used in respiratory monitoring masks to detect the respiratory cycle, or in protective gloves. The sensor can also be a strain sensor, which can be used in joint braces to track motion angles.
[0063] The following examples and comparative examples will further illustrate the preparation method of the thermoelectric device of the present invention and the performance of the obtained thermoelectric device.
[0064] In step S1 of the method for preparing the thermoelectric device provided in the first embodiment, the electrospinning solution is formed by dissolving 2.5g of thermoplastic polyurethane particles in an organic solvent, wherein the organic solvent includes 3.75ml of N,N-dimethylformamide and 3.75ml of tetrahydrofuran, and the mass percentage of thermoplastic polyurethane in the resulting electrospinning solution is 25wt%. The conductive liquid is formed by mixing and ultrasonically dispersing 0.32ml of a 10wt% multi-walled carbon nanotube aqueous dispersion, 0.615ml of a 1.3wt% poly(3,4-ethylenedioxythiophene):polystyrene sulfonate aqueous dispersion, and 9.065ml of deionized water. The mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate is 4:1, and the solid content of the conductive liquid is 4mg / ml.
[0065] In step S2, the electrospinning time is 1 hour, the voltage is 12kV to 15kV, the inner diameter of the electrospinning nozzle is 0.8mm, the distance between the electrospinning nozzle and the collector is 20cm, and the flow rate of the electrospinning solution is 2ml / h. Additionally, the ambient temperature during step S2 is 40℃ to 50℃, and the relative humidity is 30% to 40%. After this step, a scanning electron microscope image of the fiber membrane 20 is obtained, as shown in the image. Figure 3 As shown. By Figure 3 As can be seen, the fiber membrane 20 exhibits a uniform and dense fiber network, providing a favorable foundation for the construction of a conductive network.
[0066] In step S3, the amount of conductive liquid sprayed is 5 ml, the nozzle diameter of the air spraying device is 0.5 mm, the air pressure is 0.3 MPa, and the distance from the nozzle to the fiber membrane 10 is 15 cm. A hot air drying oven is used in this step for drying at 50°C for 20 minutes.
[0067] The number of times steps S2 and S3 are repeated is 5.
[0068] In step S4, the primary fiber membrane-conductive filler composite is immersed in the conductive liquid for 30 minutes. A vacuum drying oven is used in this step for drying at 50°C for 60 minutes. After this step, a scanning electron microscope image of the fiber membrane-conductive filler composite is obtained, as shown in the image below. Figure 4 As shown. By Figure 4 As can be seen, the conductive layer 20 and the conductive filler filling the pores of the fiber membrane 10 together form a continuous and dense three-dimensional conductive network.
[0069] In step S5, the preset shape is a rectangle of 50mm × 10mm. Two sub-devices are connected using copper foil electrodes, and silver paste is applied to the junction between the copper foil electrodes and the sub-devices. Finally, a 50μm thick polyimide film is used for encapsulation.
[0070] After step S5 is completed, the thermoelectric device is subjected to performance testing. Specific tests include testing the conductivity and Seebeck coefficient of the thermoelectric device, and the results are as follows: Figure 5 As shown in Table 1; the open-circuit voltage output performance of the thermoelectric device was tested at temperature differences (ΔT) of 10K, 16K, and 22K, and the results are as follows. Figure 6 As shown; the tensile properties of the thermoelectric device were tested, and the results are as follows. Figure 7 As shown in Table 1; the voltage response performance of the thermoelectric device was tested when applied to a finger joint with a temperature difference of 10K and the finger was bent at 45° and 90°. The results are as follows. Figure 8 As shown.
[0071] The difference between the preparation method of the thermoelectric device provided in the second embodiment and that in the first embodiment lies only in the conductive liquid provided in step S1. In this embodiment, the conductive liquid is formed by mixing and ultrasonically dispersing 0.2 ml of a 10 wt% multi-walled carbon nanotube aqueous dispersion, 1.538 ml of a 1.3 wt% poly(3,4-ethylenedioxythiophene):polystyrene sulfonate aqueous dispersion, and 8.262 ml of deionized water, under the same ultrasonic conditions as in the first embodiment. That is, the mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid of this embodiment is 1:1.
[0072] The thermoelectric device prepared in this embodiment was subjected to performance testing. Specific tests included testing the conductivity and Seebeck coefficient of the thermoelectric device, and the results are as follows: Figure 5 As shown; the tensile properties of the thermoelectric device were tested, and the results are as follows. Figure 7 As shown.
[0073] The difference between the preparation method of the thermoelectric device provided in the third embodiment and that in the first embodiment lies only in the conductive liquid provided in step S1. In this embodiment, the conductive liquid is formed by mixing and ultrasonically dispersing 0.08 ml of a 10 wt% multi-walled carbon nanotube aqueous dispersion, 2.462 ml of a 1.3 wt% poly(3,4-ethylenedioxythiophene):polystyrene sulfonate aqueous dispersion, and 7.458 ml of deionized water, under the same ultrasonic conditions as in the first embodiment. That is, the mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid in this embodiment is 1:4.
[0074] The thermoelectric device prepared in this embodiment was subjected to performance testing. Specific tests included testing the conductivity and Seebeck coefficient of the thermoelectric device, and the results are as follows: Figure 5 As shown; the tensile properties of the thermoelectric device were tested, and the results are as follows. Figure 7 As shown.
[0075] The difference between the preparation method of the thermoelectric device in the first comparative example and the first embodiment lies only in the conductive liquid provided in step S1. In this comparative example, the conductive liquid is formed by mixing and ultrasonically dispersing 0 ml of a 10 wt% multi-walled carbon nanotube aqueous dispersion, 3.077 ml of a 1.3 wt% poly(3,4-ethylenedioxythiophene):polystyrene sulfonate aqueous dispersion, and 6.923 ml of deionized water, under the same ultrasonic conditions as the first embodiment. That is, the mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid of this embodiment is 0:10. The scanning electron microscope image of the fiber membrane-conductive filler composite prepared in this comparative example is shown below. Figure 9 As shown.
[0076] The conductivity and Seebeck coefficient of the thermoelectric device prepared in this comparative example were tested, and the results are as follows: Figure 5 As shown.
[0077] The difference between the preparation method of the thermoelectric device in the second comparative example and the first embodiment lies only in the conductive liquid provided in step S1. In this comparative example, the conductive liquid is formed by mixing and ultrasonically dispersing 0.4 ml of a 10 wt% multi-walled carbon nanotube aqueous dispersion, 0 ml of a 1.3 wt% poly(3,4-ethylenedioxythiophene):polystyrene sulfonate aqueous dispersion, and 9.6 ml of deionized water, under the same ultrasonic conditions as the first embodiment. That is, the mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid of this embodiment is 10:0. The scanning electron microscope image of the fiber membrane-conductive filler composite prepared in this comparative example is shown below. Figure 10 As shown.
[0078] The conductivity and Seebeck coefficient of the thermoelectric device prepared in this comparative example were tested, and the results are as follows: Figure 5 As shown.
[0079] The third comparative example provides a method for fabricating a thermoelectric device, the only difference between which is the first embodiment: the impregnation step is omitted (i.e., step S4 is omitted), and the composition of the conductive liquid is the same as in the first embodiment. The conductive liquid is only sprayed to form a surface conductive layer, without filling the fiber pores.
[0080] The thermoelectric device prepared in this embodiment was subjected to performance testing. Specific tests included testing the conductivity and Seebeck coefficient of the thermoelectric device, and the results are as follows: Figure 5 As shown.
[0081] The fourth comparative example provides a method for fabricating a thermoelectric device, the only difference between which is the omission of the spraying step (i.e., step S3) and the same composition of the conductive liquid as the first embodiment. The conductive liquid only fills the fiber pores through impregnation, without constructing interlayer conductive channels.
[0082] The thermoelectric device prepared in this embodiment was subjected to performance testing. Specific tests included testing the conductivity and Seebeck coefficient of the thermoelectric device, and the results are as follows: Figure 5 As shown.
[0083] The fifth comparative example was conducted using the method disclosed in "Highly Stretchable, Sensitive, and Multifunctional Thermoelectric Fabric for Synergistic-Sensing Systems of Human Signal Monitoring" by Cui, Y.; He, X.; Wang, Q. et al. in *Advanced Fiber Materials*. The thermoelectric devices obtained in this comparative example underwent performance testing, specifically measuring their conductivity, Seebeck coefficient, and tensile properties. The test results are shown in Table 1.
[0084] The sixth comparative example was conducted using the method disclosed in the paper "MXene-based thermoelectric fabric integrated with temperature and strain sensing for health monitoring" by Peng, J., Ge, F., Han, W., et al. in the *Journal of Materials Science & Technology*. The thermoelectric devices obtained in this comparative example underwent performance testing, specifically measuring their conductivity, Seebeck coefficient, and tensile properties. The test results are shown in Table 1.
[0085] The seventh pair of proportions adopts the data from He, X.; Shi, J.; Hao, Y. et al. in *Carbon Energy*.
[0086] The method disclosed in "Highly Stretchable, Durable, and Breathable Thermoelectric Fabrics for Human Body Energy Harvesting and Sensing" (from the Carbon Energy journal) was implemented. Performance tests were conducted on the thermoelectric device obtained in this comparative example, specifically testing the conductivity, Seebeck coefficient, and tensile properties of the obtained thermoelectric device. The test results are shown in Table 1.
[0087] The eighth comparative example was performed using the method disclosed by Shalini V, Roghan R. et al. in *Materials Chemistry and Physics*, in their paper "Solution processed polyaniline anchored graphene on conductive carbon fabric for high performance wearable thermoelectric generators". The thermoelectric device obtained in this comparative example underwent performance testing, specifically measuring its conductivity, Seebeck coefficient, and tensile properties. The test results are shown in Table 1.
[0088] The ninth pair of proportions adopts the "Development of polypyrrole-coated cotton thermoelectric fabrics" proposed by Jangra, V.; Vishnoi, P.; Maity, S. et al. in *The Journal of The Textile Institute*.
[0089] The method disclosed in (Development of Polypyrrole Coated Cotton Thermoelectric Fabric) was implemented. Performance tests were conducted on the thermoelectric device obtained in this comparative example, specifically including tests on the electrical conductivity, Seebeck coefficient, and tensile properties of the obtained thermoelectric device. The test results are shown in Table 1.
[0090] Table 1
[0091]
[0092] contrast Figure 4 , Figure 9 and Figure 10As can be seen, although a three-dimensional conductive network is also formed in the fiber membrane-conductive filler polymers prepared in the first and second comparative examples, the continuity and density are inferior to the three-dimensional conductive network in the fiber membrane-conductive filler polymer prepared in the first embodiment.
[0093] Depend on Figure 5 As can be seen, with the increase of the mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid, the conductivity of the thermoelectric device first increases and then decreases, while the Seebeck coefficient first increases and then decreases. By adjusting the mass ratio of multi-walled carbon nanotubes to poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid, it is possible to achieve a balance between the conductivity and the Seebeck coefficient of the thermoelectric device. Figure 5 It can also be seen that the conductivity of the thermoelectric device prepared in the first embodiment is significantly higher than that of the thermoelectric device prepared in the third comparative example and the thermoelectric device prepared in the fourth comparative example, proving that the three-dimensional conductive network prepared by the spraying and impregnation process has better continuity and has a synergistic enhancement effect on carrier migration.
[0094] Depend on Figure 6 As can be seen, the Seebeck coefficient of the thermoelectric device prepared in the first embodiment exhibits a good linear relationship with the temperature gradient, indicating that the thermoelectric device can stably convert the temperature difference into a voltage signal, and thus can be applied to a temperature sensor.
[0095] Depend on Figure 7 As can be seen, the tensile strength of the thermoelectric devices prepared in each embodiment is above 20 MPa, and the elongation at break is above 200%. That is, the thermoelectric devices prepared in each embodiment have good flexibility, can be applied to wearable devices, and can adapt to long-term deformation and stable operation under complex human movement scenarios.
[0096] Depend on Figure 8 As can be seen, the thermoelectric device prepared in the first embodiment exhibits significant differences in output voltage at different finger bending angles. This phenomenon stems from the continuous three-dimensional conductive network constructed by the combined spraying and impregnation process. The conductive layer 20 formed by spraying ensures stable transmission of longitudinal electrical signals during stretching, while the conductive filler filling the pores of the fiber membrane ensures the continuity of lateral conductivity. When the thermoelectric device deforms, the three-dimensional conductive network can precisely respond to the degree of deformation through subtle changes in the conductive pathways within or between layers, causing the output voltage to fluctuate regularly with the bending angle. This indicates that the continuous three-dimensional conductive network is key to achieving high-sensitivity stretch sensing in the thermoelectric device, enabling it to accurately track finger joint movement and deformation. Furthermore, it can be applied to strain sensors, providing reliable signal support for sports biomechanical analysis and health monitoring.
[0097] As can be seen from Table 1, compared with the various processes for preparing thermoelectric devices in the prior art, the thermoelectric device prepared in the first embodiment has good mechanical properties, good electrical conductivity and good Seebeck coefficient. It can solve the industry problem that it is difficult to balance the thermoelectric and mechanical properties of traditional thermoelectric devices, and provide an ideal sensing material with high sensitivity, strong flexibility and long-term reliability for smart wearable devices.
[0098] While the present invention has been disclosed above, it is not limited thereto. Those skilled in the art can make various modifications and variations to the present invention without departing from its spirit and scope. Therefore, if such modifications and variations fall within the scope of the claims and their equivalents, the present invention also intends to include such modifications and variations.
Claims
1. A method for fabricating a thermoelectric device, characterized in that, include: The electrospinning solution and the conductive liquid are provided; the electrospinning solution comprises thermoplastic polyurethane; the conductive liquid comprises multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate. The electrospinning solution is electrospinned to obtain a fiber membrane; The conductive liquid is sprayed onto the surface of the fiber membrane and dried to form a conductive layer; The steps of electrospinning, spraying, and drying are repeated to obtain a primary fiber membrane-conductive filler composite; the primary fiber membrane-conductive filler composite comprises alternately stacked fiber membranes and conductive layers; The primary fiber membrane-conductive filler composite is immersed in the conductive liquid, then removed, washed, and dried to obtain the fiber membrane-conductive filler composite. The fiber membrane-conductive filler composite is cut into multiple sub-devices with a predetermined shape, and the multiple sub-devices are connected by a conductor.
2. The method for preparing the thermoelectric device according to claim 1, characterized in that, The mass percentage of thermoplastic polyurethane in the electrospinning solution is 23wt% to 27wt%; and / or, The solid content of the conductive liquid is 3 mg / ml to 5 mg / ml.
3. The method for preparing the thermoelectric device according to claim 1 or 2, characterized in that, The electrospinning solution is formed by dissolving thermoplastic polyurethane particles in an organic solvent; The organic solvent comprises N,N dimethylformamide and tetrahydrofuran, and the volume ratio of N,N dimethylformamide to tetrahydrofuran is 1:(0.8–1.2); or, The organic solvent comprises N,N dimethylformamide and acetone, and the volume ratio of N,N dimethylformamide to acetone is 1:(0.8–1.2); or, The organic solvent includes dimethylacetamide and tetrahydrofuran, and the volume ratio of dimethylacetamide to tetrahydrofuran is 1:(0.8 to 1.2).
4. The method for preparing the thermoelectric device according to claim 1 or 2, characterized in that, The conductive liquid is formed by ultrasonically dispersing multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in deionized water; The mass ratio of multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid is greater than 0 and less than 10.
5. The method for preparing a thermoelectric device according to claim 4, characterized in that, The mass ratio of multi-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate in the conductive liquid is one of 1:4, 1:1, or 4:
1.
6. The method for preparing a thermoelectric device according to claim 1, characterized in that, The voltage during electrospinning is 12kV to 15kV; the distance between the electrospinning nozzle and the collector for fiber deposition is 15cm to 20cm; the flow rate of the electrospinning solution is 1.5ml / h to 2.5ml / h; the thickness of the fiber membrane is 25μm to 100μm; and / or, The number of repetitions of the electrospinning, spraying, and drying steps is less than or equal to 7.
7. The method for preparing a thermoelectric device according to claim 1, characterized in that, When the conductive liquid is sprayed onto the surface of the fiber membrane, the amount of conductive liquid sprayed is 3ml to 8ml, and the coverage of the conductive liquid on the surface of the fiber membrane is greater than or equal to 95%.
8. The method for preparing a thermoelectric device according to claim 1, characterized in that, The primary fiber membrane-conductive filler composite is immersed in the conductive liquid for 30 min to 60 min.
9. A thermoelectric device, characterized in that, The thermoelectric device is fabricated using the method described in any one of claims 1-8; the electrical conductivity of the thermoelectric device is greater than or equal to 80 S·m. -1 The Seebeck coefficient is 20 μV·K. -1 ~25μV·K -1 The power factor is 30 nW·m -1 ·K -2 ~70 nW·m -1 ·K -2 Tensile strength greater than or equal to 20 MPa, and elongation at break greater than 200%.
10. An application of the thermoelectric device as described in claim 9.